2016
DOI: 10.1155/2016/6745618
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture in the Treatment of a Female Patient Suffering from Chronic Schizophrenia and Sleep Disorders

Abstract: Background. The use of acupuncture in the treatment of sleep disorders in patients with chronic schizophrenia is investigated. Case Presentation. We report the case of a 44-year-old female outpatient of German origin who had been suffering from long-term schizophrenia and sleep disorders. The patient was treated with manual acupuncture weekly for 12 weeks, and a psychological assessment was performed before, immediately after, and three months after the acupuncture treatment period. In addition, actiwatch data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 33 publications
0
16
1
Order By: Relevance
“…Finally, the present review shows that positive results have been reported in the literature for the treatment of the co-morbid sleep disorders of patients with schizophrenia [35,[43][44][45]61]. For instance, the following sleep variables, i.e., sleep onset latency, sleep percentage, mean activity level, wake time after sleep onset, mean number of wake episodes, mean wake episode and longest wake episode, have been found to be significantly improved after acupuncture treatment [61].…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Finally, the present review shows that positive results have been reported in the literature for the treatment of the co-morbid sleep disorders of patients with schizophrenia [35,[43][44][45]61]. For instance, the following sleep variables, i.e., sleep onset latency, sleep percentage, mean activity level, wake time after sleep onset, mean number of wake episodes, mean wake episode and longest wake episode, have been found to be significantly improved after acupuncture treatment [61].…”
Section: Discussionmentioning
confidence: 69%
“…As can be seen in Figure 1, our search resulted in 97 articles, of which 38 articles were relevant, but only 26 of those 38 satisfied the inclusion criteria and were, thus, eligible for inclusion in this review. Of the 26, 7 were randomized controlled trials [32][33][34][35][36][37][38], 12 were case studies [39][40][41][42][43][44][45][46][47][48][49][50], and 7…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations